Rating and valuation - Lisney, Harry (Statistical and Social Inquiry Society of Ireland, 1939)
As the title suggests the scope of my subject is to inquire whence rating came, the development and the method of apportioning the demand made by the community upon its members for contribution to the common good or to the achievement of a common purpose. The question naturally and inevitably arises, in what proportion should each individual contribute, and how shall that proportion be ascertained.
Read on Thursday, 23rd February, 1939
Keywords: Valuation; Local rates; 314.15